The promise of CD4(+)FoxP3(+) regulatory T-cell manipulation in vivo: applications for allogeneic hematopoietic stem cell transplantation - Copsel, Sabrina (Haematologica, 2019)
CD4(+)FoxP3(+) regulatory T cells (Tregs) are a non-redundant population critical for the maintenance of self-tolerance. Over the past decade, the use of these cells for therapeutic purposes in transplantation and autoimmune disease has emerged based on their capacity to inhibit immune activation. Basic science discoveries have led to identifying key receptors on Tregs that can regulate their proliferation and function. Notably, the understanding that IL-2 signaling is crucial for Treg homeostasis promoted the hypothesis that in vivo IL-2 treatment could provide a strategy to control the compartment. The use of low-dose IL-2 in vivo was shown to selectively expand Tregs versus other immune cells. Interestingly, a number of other Treg cell surface proteins, including CD28, CD45, IL-33R and TNFRSF members, have been identified which can also induce activation and proliferation of this population. Pre-clinical studies have exploited these observations to prevent and treat mice developing autoimmune diseases and graft-versus-host disease post-allogeneic hematopoietic stem cell transplantation. These findings support the development of translational strategies to expand Tregs in patients. Excitingly, the use of low-dose IL-2 for patients suffering from graft-versus-host disease and autoimmune disease has demonstrated increased Treg levels together with beneficial outcomes. To date, promising pre-clinical and clinical studies have directly targeted Tregs and clearly established the ability to increase their levels and augment their function in vivo. Here we review the evolving field of in vivo Treg manipulation and its application to allogeneic hematopoietic stem cell transplantation.